The Impact of Sustainable Development on Competitive Advantage: An Empirical Study of Vocational and Skill Shortages in the Vietnam Hospitality Sector - Kim Thoa, Nguyen (Digital Repository of Theses - SSBM Geneva, 2025)
The tourism industry has grown significantly in recent years and has become a multibillion-dollar sector in many countries. As a result, hospitality services have gained increased attention, as they play a crucial role in the growth of the tourism industry. To provide high-quality services to meet the growing demands of customers, well-trained and qualified staff are required in various areas such as restaurants, hotels, and kitchens. The increase in people's incomes and interest in leisure trips has resulted in a rising demand for luxurious and high-quality accommodations, which has led to the development of luxurious hotels and resorts in Vietnam's hospitality industry. Despite the growth of the hospitality industry in Vietnam, there is a shortage of well-trained staff in the field. This is a major concern for managers and hotel owners, who are struggling to find suitable employees. Educators are also aware of the need to equip graduates with the necessary skills and qualifications to secure jobs in the industry. However, the question of skill shortages among in-service staff remains a challenge for stakeholders, and research is needed to bring new solutions to the forefront. It is important to note that the staff play a crucial role in determining the competitiveness of a firm in the market. Therefore, training them is a crucial task in the hospitality industry. Despite the significance of the area, there has been limited research done in Vietnam regarding five-star hotels and resorts, leaving the suitability of staff qualifications and skills for the development of luxurious accommodations questionable. To fill this gap in the existing literature, a study was carried out to investigate the strengths and weaknesses of hotel staff in 12 different five-star hotels and resorts across the country. The study involved 389 staff, hotel managers, owners, and supervisors and aimed at understanding the impact of experience on staff skills. The participants were divided into three sub-groups: fresh graduates, two-year-experienced staff, and five-year practitioners. Their perspectives on perceived skill mastery and disappearance were examined through questionnaires to confirm the matches and mismatches between hotel leaders and subordinates. The data collected through the study was analyzed, and the researcher concluded the skill set that was enhanced or eroded. The research provides important implications for educators and hotel managers. It highlights the need for investment in and changes to training courses and vocational programs to ensure that top employees are produced. Furthermore, the study provides guidance for staff members themselves to be aware of their strengths and weaknesses and to address any personal problems to achieve higher positions and goals in their careers.